Post Cholecystectomy Gossypiboma Mimicking a Liver Hydatid Cyst: - Yagmur, Y; Akbulut, S; Gumus, S (2015)
Background: Gossypiboma is the term for forgotten textile products such as a surgical sponge and compress in the body cavity after a surgical procedure. Objectives: The aim of this study was to evaluate previously published articles related to post cholecystectomy gossypiboma. Materials and Methods: We conducted a systematic search using PubMed, Medline, Google and Google Scholar on post cholecystectomy gossypiboma. The keywords used were: gossypiboma and cholecystectomy, textiloma and cholecystectomy and post cholecystectomy gossypiboma. Furthermore, we also present a new case of post cholecystectomy gossypiboma. Results: A total of 32 articles concerning 38 patients with post cholecystectomy gossypiboma that met the aforementioned criteria were included. Detailed intraoperative findings and surgical management were provided. The patients were aged from 26 to 79 years (Mean +/- SD: 47 +/- 13.6 years); 32 were female and six were male. The time from the causative operation to presentation with a retained surgical sponge ranged from one to 480 months (Mean +/- SD: 56.5 +/- 93.5 months). Conclusions: Gossypiboma may not be symptomatic for many years or could be symptomatic for a short duration of time. Besides being a rare surgical complication, gossypiboma can lead to serious morbidity and mortality that may cause medico-legal problems. Diagnosis with imaging methods is difficult. C1 [Yagmur, Yusuf; Gumus, Serdar] Diyarbakir Educ & Res Hosp, Dept Surg, Diyarbakir, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplantat Inst, Dept Surg, Malatya, Turkey.